2008
DOI: 10.1038/bjp.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of liquiritigenin as a consequence of the inhibition of NF‐κB‐dependent iNOS and proinflammatory cytokines production

Abstract: Background and purpose: Glycyrrhizae radix has been widely used as a cytoprotective, plant-derived medicine. We have identified a flavanoid, liquiritigenin, as an active component in extracts of Glycyrrhizae radix. This research investigated the effects of liquiritigenin on the induction of inducible NOS (iNOS) and proinflammatory cytokines by lipopolysaccharide (LPS) in Raw264.7 cells, and on paw oedema in rats. Experimental approach: iNOS expression was determined by western blotting, real-time reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
144
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(159 citation statements)
references
References 46 publications
11
144
1
3
Order By: Relevance
“…In a previous study, Kim et al showed that liquiritigenin exerted anti-inflammatory effects against lipopolysaccharide in Raw264.7 cells at a concentration ranging from 3 to 30 μmol/L [18] . We reckon that the differences in effective dose observed in the two studies may be due to the use of different cells and/or different toxic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Kim et al showed that liquiritigenin exerted anti-inflammatory effects against lipopolysaccharide in Raw264.7 cells at a concentration ranging from 3 to 30 μmol/L [18] . We reckon that the differences in effective dose observed in the two studies may be due to the use of different cells and/or different toxic factors.…”
Section: Discussionmentioning
confidence: 99%
“…ERβ is expressed in brain centers related to learning and memory and is less likely than ERα to be related to sexual function [14,15] . Second, liquiritigenin has been shown in several studies to exert cytoprotective effects [16,17] ; recent studies demonstrate that liquiritigenin exerts anti-inflammatory effects through the NF-κB pathway [18] . Third, we previously observed that liquiritigenin did not induce proliferation of MCF-7 and T47D breast cancer cells (data not shown), which is consistent with other studies [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Liquiritigenin has various beneficial properties such as hepatoprotective [1], anti-cancer [6,7] and anti-inflammatory activity [4]. SIRT1 is a NAD + -dependent protein deacetylase that is involved in the regulation of gene expression, cell metabolism, and differentiation in many organisms including yeast, bacteria, and humans [36].…”
Section: Activation Of Sirt1 Expressionmentioning
confidence: 99%
“…It was found that liquiritin exist mainly as glucoside form of bioactive compound [4,5], while liquiritigenin, an aglycone of liquiritin is present in small amounts in G. uralensis [1]. There are several studies on their beneficial effects including prevention of carcinogenesis [6,7], hepatoprotective effects [1], and anti-inflammatory effects [4].…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizin (GL), a major and active constituent of licorice root, has many attributed pharmacological effects, including anti-inflammatory [8] , anti-allergy [9] , and anti-viral activities [10] , which may be due to the steroid-like structure of 18β-glycyrrhetinic acid. Therefore, we hypothesized that GL could interact with β 2 -AR agonists at both the molecular and receptor level in a manner similar to glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%